STUDENTS’ PERCEPTION OF LECTURERS’ TONE OF VOICE AS A STYLE OF COMMUNICATION IN TEACHING ENGLISH DURING VIRTUAL MEETING SESSIONS - Ardin Saputra; Amra Ariyani; Hasriani G (Universitas Negeri Makassar, 2023)
This study aimed to find out the students’ perception of the lecturer's tone of voice as a style of communication in teaching English during virtual meeting sessions for English education students, at Universitas Negeri Makassar. This study used a descriptive qualitative method. The participants in this study were third-year students. The data was collected through interviews. Based on the general results of the interviews, the participants gave positive perceptions. The results of the data showed that students have a positive perception of lecturers’ tone of voice as a style of communication in teaching English during virtual meeting sessions.